Increasing Organizational Commitment Through Strengthening Organizational Culture And Learning Organization - Lina Novita, Elly Sukmanasa (International Journal of Management, Innovation, and Education, 2023)
Commitment of teacher's organization is very important because through commitment a teacher can become more responsible for his main duties and functions than those who do not have commitment to the organization. The existing phenomenon is that the teacher's commitment to the organization has not been as expected. The desire to develop and build quality schools is still low, so it is still far from expectations. The purpose of this study is to find efforts to increase organizational commitment in East Jakarta State Senior High Schools through the strengtenth of organizational culture, learning organization and personality. These efforts are made through the identification of the strengths between these variables. This research is a combination study using a correlational approach and SITOREM Analysis. Correlational statistical methods are used to determine whether organization culture, learning organization and personality variables have a positive relationship with organizational commitment. The SITOREM analysis is used to determine the order of priorities and the recommendations for improvement of the indicators needed. The results of the study show that there is a relationship between organizational commitment and organizational culture and learning organization. This means that to increase organizational commitment, good organizational culture and organizational learning are needed.